A. x= - √14/3 -4
B. x= - √10/3
c. x= √14-4/3
d. x=√10/3
e. x= - √14-4/3
f. x= √14/3-4
(3x + 4)2 = 14
(3x + 4)2 means that 2 will multiply both 3x and 4
2 * 3x = 6x 2 * 4 = 8
6x + 8 = 14
Move +8 to the other side of the equation
6x = 14 - 8 Note : Moving +8 to the other side will change the sign in front of it, that is from + to -
6x = 14 - 8
6x = 6
Divide both sides by 6 because of the 6 beside the x : 6x
6x/6 = 6/6
x = 1
Answer:
The translation is left 4 units
Step-by-step explanation:
we know that
Is a vertical parabola open upward with vertex at (15,3)
Is a vertical parabola open upward with vertex at (11,3)
so
The rule of the translation of (15,3) ----> (11,3) is equal to
(x,y) ----> (x-4,y)
That means ----> The translation is left 4 units
Answer:
left 4 units
Step-by-step explanation:
a - the constant of proportionality
We have the constant of proportionality a = 0.7.
Therefore the equation is:
Answer:
y= 0.7x ...................................................................................
*What is the perimeter of the triangle in cm only?
*What is the perimeter of the triangle in mm only?